A digital loonie among many digital currencies prospects and outlook - Pierre L. Siklos (Centre for International Governance Innovation (CIGI), 2022)
Global interest in digitalization is growing in response to the COVID-19 pandemic and driving central banks to introduce retail central bank digital currencies (CBDCs). The successful rollout of retail CBDCs will depend on each country's institutional capacity and the scope of international cooperation and regulation. Retail CBDCs are unlikely to replace domestic currencies but instead complement notes and coins in circulation, offering greater convenience and lower transactions costs.
Keywords: 330